Efeito da intensidade luminosa no desenvolvimento larval do camarão-da-amazônia, macrobrachium amazonicum - de Araujo, Mariana Cutolo; Valenti, Wagner Cotroni [UNESP] (My University, 2011)
The effects of four light intensities (0; 2.8 ± 0.9; 5,5 ± 1,8 e 7,8 ± 2,5 1mol s-1 m-2, about 136.5 ± 87.5; 273 ± 43.8 e 390 ± 125 lux, respectively) on survival, productivity, weight gain and larval development of Macrobrachium amazonicum were investigated. Four treatments with three replicate tanks were evaluated. Newly hatched larvae were held in black tanks (80.2 ± 0.6 larvae L-1) filled with 50-L-brackish water (salinity of 10), in a recirculating system. Tanks were covered with shadow cloth allowing 35% and 70% light, respectively, to reach light intensities of 2.8 ± 0.9 and 5.5 ± 1.8 1mol s-1 m-2 at the water surface. Complete absence of light (0 1mol s-1 m-2) was obtained covering the tanks with opaque black plastic, and full-light condition used no covering (7.8 ± 2.5 1mol s-1 m-2). Observations showed that the survival rate was not affected by light intensity. Productivity and weight gain were higher under 7.8 ± 2.5 1mol s-1 m-2 light intensity than under 0 and 2.8 ± 0.9 1mol s-1 m-2 intensities (P<0.05). The larval development index was similar among the treatments under the different light intensities. However, from stage VII this index was increased slightly in the treatment under 7.8 ± 2.5 1mol s-1 m-2 light intensity. In conclusion, light intensity affects larval development of M. amazonicum. Values as high as 7.8 1mol s-1 m-2 (about 390 lux) improve the larval performance by enhancing development, productivity and weight gain compared to lower values.
The effects of light intensities on larval development of amazon river prawn, macrobrachium amazonicum
Keywords: Amount of light; Freshwater prawn; Laboratory; Larviculture